2 Answers | Add Yours
The quadratic equation 2x^2+14=0 has to be solved.
=> 2(x^2 + 7 ) = 0
x^2 + 7 = 0
=> x^2 = -7
=> x = `sqrt(-7)` and x = `-sqrt(-7)`
=> x = `sqrt7*i` and x = `-sqrt7*i`
The solution of the equation 2x^2+14=0 is x = `sqrt7*i ` and `x = -sqrt 7*i`
`2x^2 + 14 =0`
`2(x^2 +7)= 0`
As the equation is equal to zero, each factor equals zero. Thus:
`therefore x= +- sqrt (-7)`
`therefore` thre is no normal solution for this equation due to the negative symbol inside the square root.
`therefore` no solution or if you use complex numbers = `isqrt7`
We’ve answered 330,781 questions. We can answer yours, too.Ask a question